A Challenging Classic Coupling: Esterification of Camphoric Acid - a Steric - Hindered Polar Carboxylic Acid and Solanesol - a Long - Chain Nonpolar Alcohol. - Hoa, Phung Nhu; Trang, Nguyen Thi Thu; Anh, Nguyen Tien Tuan; Phong, Pham Van; Ky, Nguyen Van (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 4, 2016)
Abstract: